Тематика з історії козацтва на сторінках наукової періодики 1950–1980-х рр.: Українській історичний журнал - Присяжнюк, Ю. (Чорноморська минувшина, 2023)
У статті розглянуто основні аспекти вивчення теми козацтва в українських історичних наукових виданнях протягом 50-80 років XX ст. та проведено аналіз рівня вивченості проблем козацтва на сторінках «Українського історичного журналу». Досліджено роль цього часопису у розгляді питань соціально-економічного, політичного та культурного розвитку українських земель у пізньому середньовіччі. Аналізується еволюція дослідницьких підходів, розкриваються ключові теми та питання, що були актуальними для істориків протягом визначеного періоду. Висвітлюються внески окремих вчених та їх вплив на загальний науковий дискурс щодо козацтва в Україні в зазначений історичний період. Виділено важливість студій зі спеціальних історичних дисциплін для освітлення історії України в період козаччини. Визначено, що автори цих студій істотно розширили дослідження з конкретно-історичних проблем досліджуваного періоду, роз'яснили та уточнили низку явищ і подій історії козацтва. Зроблено висновок, що «Український історичний журнал», який займає важливе місце вітчизняній історіографії, вніс значний внесок у вивчення важливих аспектів козацтва України. Дана стаття вносить важливий внесок у розуміння розвитку історичного дослідження козацької тематики та визначає його місце у науковому обговоренні протягом зазначеного часового проміжку. The article examines the main aspects of the study of the topic of Cossacks history in Ukrainian historical scientific publications during the 50-80 years of the 20th century. and an analysis of the level of study of the problems of the Cossacks on the pages of the "Ukrainian Historical Journal" was carried out. The role of this periodical in considering the issues of socio-economic, political and cultural development of Ukrainian lands in the late Middle Ages is studied. The evolution of research approaches is analyzed, the key topics and questions that were relevant for historians during a certain period are revealed. The contributions of individual scientists and their influence on the general scientific discourse regarding the Cossacks in Ukraine in the specified historical period are highlighted. The importance of studies in special historical disciplines for illuminating the history of Ukraine during the Cossack period is highlighted. It was determined that the authors of these studies significantly expanded research on specific historical problems of the period under study, clarified and specified a number of phenomena and events in the history of the Cossacks. It was concluded that the "Ukrainian Historical Journal", which occupies a unique place in national historiography, made a significant contribution to the study of important aspects of the Cossacks of Ukraine. This article makes an important contribution to the understanding of the development of historical research on the Cossack theme and determines its place in the scientific discussion during the specified time period.